Recruitment and monitoring behaviors by leaders predict following in wild Barbary macaques (Macaca sylvanus) - A. Seltmann; M. Franz; B. Majolo; M. Qarro; J. Ostner; O. Schülke (Primate Biology, 2016)
For group-living animals it is essential to maintain the cohesiveness of the group when traveling. Individuals have to make an accurate decision about where and when to move. Communication before and during the departure of the first individual may play a crucial role in synchronizing a collective movement. We hypothesized that individuals in a wild primate group use signals or cues prior to and after departure to achieve collective movements. With two observers we used all-occurrences behavior sampling of collective movements in a group of wild Barbary macaques (Macaca sylvanus) in the Middle Atlas, Morocco. The number of individuals displaying pre-departure behavior predicted the success of an initiation of a collective movement. Pauses of the first departing individual after departure enhanced following behavior and might have served as recruitment signal. However, the opposite was the case for back-glancing, which functions as a monitoring signal in other species. Because in our study frequently back-glancing individuals were also less socially integrated, back glances may better be interpreted as indicators of hesitation and insecurity. To successfully initiate a collective movement, it seemed to be sufficient for a socially integrated group member to take action when other group members signal their willingness prior to departure and to occasionally wait for the group while moving.